Analisis Tingkat Kesehatan PT Bank BTPN Syariah dengan Menggunakan Metode RGEC - Amalia, Firdha Ikhlazul; Maharany, Indah Dewi (BISNIS, 2023)
With the development of advanced Islamic banks in Indonesia, it is necessary to supervise each Islamic bank and see how the condition of the bank in carrying out its business activities. Islamic banks must be assessed for their performance and soundness level so that banks can carry out their functions normally, such as channeling funds, collecting funds, supporting the smooth flow of payment traffic, and maintaining economic and monetary stability. The researcher took BTPN Syariah as the research sample, which met the criteria as a Sharia Commercial Bank registered in JII70 and published annual report for 2016 – 2020. The research type and approach that used in is descriptive quantitative research. Data collection techniques used are documentation techniques and literature study. The results of this research indicate that the soundness level of PT Bank BTPN Syariah in 2016 with a weight of 80% received PK 2 with the predicate "healthy", and in 2017, 2018, 2019, and 2020 with the same weight of 91.42% received PK 1 with the predicate "very healthy".